2011
DOI: 10.1016/j.bcp.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant chimeric lectins consisting of mannose-binding lectin and L-ficolin are potent inhibitors of influenza A virus compared with mannose-binding lectin

Abstract: MBL structurally contains a type II-like collagenous domain and a carbohydrate recognition domain (CRD). We have recently generated three novel recombinant chimeric lectins (RCL), in which varying length of collagenous domain of mannose-binding lectin (MBL) is replaced with that of L-ficolin (L-FCN). CRD of MBL is used for target recognition because it has a broad spectrum in pathogen recognition compared with L-FCN. Results of our study demonstrate that these RCLs are potent inhibitors of influenza A virus (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…Chang et al [38] showed that recombinant chimeric lectins, consisting of an L-ficolin collagen domain and an MBL carbohydrate recognition domain, triggered a dose-dependent activation of the lectin complement pathway in the presence of influenza A virus, an observation that is consistent with our results.…”
Section: Discussionsupporting
confidence: 82%
“…Chang et al [38] showed that recombinant chimeric lectins, consisting of an L-ficolin collagen domain and an MBL carbohydrate recognition domain, triggered a dose-dependent activation of the lectin complement pathway in the presence of influenza A virus, an observation that is consistent with our results.…”
Section: Discussionsupporting
confidence: 82%
“…Three ficolins have been identified in human serum and have been quantified to be present at levels of about 5 g/ml (ficolin-2 or L-ficolin), 18 g/ml (ficolin-3 or H-ficolin), and 1 g/ml (ficolin-1 or M-ficolin), with the last value being close to that of circulating MBL (1.2 g/ml) (37)(38)(39)(40). There are few reports concerning virus recognition by ficolins, apart from the interaction of L-ficolin with hepatitis C and influenza A virus surface glycoproteins (41)(42)(43)(44).…”
Section: Importancementioning
confidence: 99%
“…In an attempt to reduce complications with the coagulation system, MBL derivatives have been produced. One such agent is recombinant chimeric lectin 4 (RCL4), a derivative of MBL in which the collagen-like domain of MBL is replaced with that of L-ficolin [7,140]. RCL4 is at least tenfold more efficient in activating the lectin complement pathway while it is significantly weaker in promoting thrombin-like activity [7].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…One such agent is recombinant chimeric lectin 4 (RCL4), a derivative of MBL in which the collagen-like domain of MBL is replaced with that of L-ficolin [7,140]. RCL4 is at least tenfold more efficient in activating the lectin complement pathway while it is significantly weaker in promoting thrombin-like activity [7]. Recent investigations in our laboratory demonstrate that RCL4 is more efficient than MBL in reducing infection with viruses, including influenza A, Ebola and Nipah [7,140].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
See 1 more Smart Citation